2003
DOI: 10.1034/j.1399-3054.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde oxidase isoforms and subunit composition in roots of barley as affected by ammonium and nitrate

Abstract: Aldehyde oxidase (AO; EC 1.2.3.1) isoforms in roots of barley plants grown on ammonium or nitrate as nitrogen sources were studied. Roots of ammonium-grown barley plants exhibited considerable levels of AO2, AO3, and AO4 activities after native PAGE. Significantly lower AO2 and AO3 activity bands were observed in roots of plants grown on nitrate. When abscisic aldehyde was used as a substrate a strong response of the AO2 band was observed as well as a faint reaction of the AO3 band, but no activity of AO4 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…GK Öthalom. In an earlier work it was reported that in the presence of IAld substrate the band of AAO1 isoform could not be detected in barley, so the band with the least mobility in our samples originates from the activity of AAO2 (Omarov et al, 2003). In our experiments, the basic activities of AO2-3 bands were more intense in the control plants and the PEG-induced isoforms exhibited much higher activities in the isohydric genotype cv.…”
Section: Aldehyde Oxidase Activitiessupporting
confidence: 57%
See 1 more Smart Citation
“…GK Öthalom. In an earlier work it was reported that in the presence of IAld substrate the band of AAO1 isoform could not be detected in barley, so the band with the least mobility in our samples originates from the activity of AAO2 (Omarov et al, 2003). In our experiments, the basic activities of AO2-3 bands were more intense in the control plants and the PEG-induced isoforms exhibited much higher activities in the isohydric genotype cv.…”
Section: Aldehyde Oxidase Activitiessupporting
confidence: 57%
“…PsAO1 and PsAO2 were mainly expressed in the leaves of pea plants, while PsAO3 was expressed in ageing leaves and seeds (Zdunek-Zastocka, 2008). Aldehyde oxidase isoforms, which use abscisic aldehyde as a physiological substrate, were identified in Arabidopsis rosette leaves (Seo et al, 2000a), and two isoforms, AO2 and AO3, were also detected in barley roots (Omarov et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Three AO isoforms (AOot, AO[3, AO7) of Arabidopsis thaliana were found to be dimers; AOot and AOy are homodimers consisting of two subunits of 150 kDa and 145 kDa, respectively, while AOI3 was shown to be a heterodimer composed of one 150 kDa and one 145 kDa subunit . Similar subunit composition was reported for three AO isoforms observed in roots of barley (Omarov et al 2003) and leaves of pea plants (Zdunek 2002). Plant AO proteins are phylogenetically closely related and form a distinct group of the phylogenetic tree when compared to other eukaryotic AO and XDH proteins (Hoff et al 1998).…”
Section: Functional Molecular and Biochemical Characteristicssupporting
confidence: 78%
“…Four cDNAs of AO genes from Arabidopsis (Sekimoto et al 1998), three putative AO genes and two AO pseudogenes from tomato (Min et al 2000;Ori et al 1997), three cDNAs from pea (Zdunek-Zastocka 2008), and one AhAO1 cDNA from peanut ) have been reported. However, isoforms that can efficiently oxidize ABAld to ABA have only been identified in Arabidopsis rosette leaves (AOδ; Seo et al 2000b), barley roots (AO2 and AO3; Omarov et al 2003), and pea roots and leaves (PAO2 and PAO3; Zdunek-Zastocka et al 2004). Among the AO genes, the expression of AAO3, TAO1, and TAO3 was increased rapidly in response to drought stress (Seo et al 2000b;Yesbergenova et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Plant AO belongs to a multigene family (Ando et al 2006;Min et al 2000;Ori et al 1997;Sekimoto et al 1997Sekimoto et al , 1998Zdunek-Zastocka 2008), whose members differ in electrophoretic mobility and subunit composition (Akaba et al 1999;Seo et al 2000b;Koiwai et al 2000;Omarov et al 2003;Zdunek-Zastocka et al 2004) and exhibit broad substrate specificity (Koiwai et al 2000;Akaba et al 1998). Plant AO has only been purified from coleoptiles of maize (Koshiba et al 1996).…”
Section: Introductionmentioning
confidence: 99%